Endothelial cell-specific molecule-1/endocan: diagnostic and prognostic value in patients suffering from severe sepsis and septic shock - Pauly, Dominic; Hamed, Sonja; Behnes, Michael; Lepiorz, Dominic; Lang, Siegfried; Akın, Ibrahim; Borggrefe, Martin; Hoffmann, Ursula (Journal of critical care, 2016)
Purpose: This study aims to assess the diagnostic and prognostic value of endocan in patients with severe sepsis or septic shock on a medical intensive care unit (ICU). Methods: 150 patients suspected for at least severe sepsis were enrolled on a medical ICU. On days 1, 3, and 8, plasma levels of endocan, procalcitonin (PCT), and interleukin (IL)-6 were measured. Follow-up on all-cause mortality was performed after 30 days and 6 months. Results: Endocan correlated with Acute Physiology and Chronic Health Evaluation II (APACHE II), Sequential Organ Failure Assessment (SOFA), and Simplified Acute Physiology Score II (SAPS II) (P < .006). Endocan was higher in patients with at least severe sepsis compared with systemic inflammatory response syndrome (SIRS) or sepsis patients (P = .0006) on days 1, 3, and 8. With a minimum sensitivity of 70%, uniform cutoff levels were set for ≥ sepsis at 1.8 ng/mL, for ≥ severe sepsis at 2.6 ng/mL, for ≥ septic shock at 2.9 ng/mL. On day 1, endocan levels of the fourth quartile were significantly associated with 30-days and 6-months mortality compared to lower levels. After adjustment in Cox regressions, endocan still revealed prognostic value. Conclusions: Endocan showed diagnostic capacity to diagnose patients with severe sepsis and septic shock and revealed prognostic information for 30-days and 6-months all-cause mortality.